Abrupt Late Holocene uplifts of the southern Izu Peninsula, central Japan: Evidence from emerged marine sessile assemblages. (March 2014) - Kitamura, Akihisa; Koyama, Masato; Itasaka, Koji; Miyairi, Yosuke; Mori, Hideki
Abstract Evidence for abrupt coastal uplifts has been found in emerged sessile assemblages in a sea cave at the southern end of the Izu Peninsula, central Japan. We identified five sessile assemblage zones: Zones I to V, in ascending order. The uppermost zone (Zone I), located at an elevation of 2.7–3.5 m above the present‐day mean sea level (amsl), is a hard massive shellcrust consisting mainly of the barnacles Chthamalus challenger and the tube worm Pomatoleios kraussii. Zone II, at 2.35–2.7 m amsl, is dominated by well‐preserved individuals of C. challenger. Zone III, at 2.0–2.35 m amsl, is strongly eroded and consists mainly of C. challenger and P. kraussii. Zone IV, at 1.6–2.0 m amsl, is characterized by the co‐occurrence of very fresh shells of C. challenger and P. kraussii. Zone V (the lowest zone), at 1.0–1.60 m amsl, is characterized by the co‐occurrence of very fresh shells of Saccostrea kegaki and P. kraussii, and by the absence of C. challenger. Radiocarbon dating by accelerator mass spectrometry (AMS) and the presence of modern taxa in the sessile assemblages suggest that three episodes of coastal uplift have occurred in the area, during AD 570–820, AD 1000–1270, and AD 1430–1660, with magnitudes of 0.9–2.0 m, 0.3–0.8 m, and 1.9–2.2 m, respectively.